Planting environment, nutrition and storage effects on yield and quality of red-husked non-basmati aromatic rice: Planting, nutrition and storage effects on aromatic rice - Saha, Bhaswati; GHOSH, MRITYUNJAY; Chakraborti, Prabir; Mukherjee, Souti; Banerjee, Sibajee (ORYZA-An International Journal of Rice, 2025)
Two separate experiments were conducted at University Farm and at Aromatic Rice Laboratory, Bidhan Chandra Krishi Vishwavidyalaya, West Bengal, India, to assess the effect of planting environment, nutrition, and storage methods on flowering behaviour, yield, and quality of red-husked non-Basmati aromatic rice (cv. Lal Badshabhog). The flowering and day length relations under varied planting times were: 10 July [D10J (105-109 d and 11.85-11.91 hr)], 25 July [D25J (102-103 d and 11.71-11.74 hr)], and 10 August [D10A (96-98 d and 11.55-11.60 hr). The mean light extinction coefficient (k) of the variety was 0.37 at the flowering stage, indicating its semi-erect leaves. Planting on D10A led to less duration (123.3 d), greater grain yield (2.72 t ha-1), amylose content(17.5%) and medium aroma (score 1.74) compared to early plantings (D10J and D25J); while close planting (S15×15, or 44 hills m-2) improved the grain yield by 4.0% over wider spacing (S20×15 or 33 hills m-2). Sole application of chemical fertilizers (N50P25K25 kg ha-1) resulted in higher grain yield and protein content (7.8%) compared to organic or integrated nutrient management. Storage of paddy for a 3-month (3-m) period in an earthen pot (CEp) had a favourable effect on head rice recovery (HRR), protein content, and aroma compared to jute-made gunny bag (CGb) ) and polypropylene bag (CPb). The cool storage environment (8±2oC) favouredgreater HRR (56.6%) and aroma in 3-m storage, while it improved HRR and elongation ratio (1.81) than ambient condition (28±4oC) during 6-m post-harvest period.